Beziehungen zwischen Reliefformung, Natur- und Nutzungspotentialen in der zentralen Chaîne de l’Atakora, NW-Benin - Heinrich, Jürgen; Moldenhauer, Klaus-Martin (ERDKUNDE, 1998)
It is well known that the recent environmental conditions of the savanna regions in Western Africa are not only caused by climatic and edaphic factors. They also depend on specific landform evolution as well as on certain human impacts. In this context, morphological and pedological studies were carried out in the Chaîne de l’Atakora in order to determine the ecological conditions in relation to landscape developement and land use. The Chaîne de l’Atakora is a thinly populated and densely wooded mountainous region in the west African savanna of NW Benin. The main parts of the Chaîne consist of metamorphic sandstones, mica shists and quarzites gently dipping SE. As a result of tectonic uplift and selective weathering, certain strata series are exposed in form of escarpments striking SSW to NNE. Due to this structure-controlled relief three major units with different geo- and pedological conditions can be distinguished: first, the steep slopes of the escarpments where shallow lithosols with low field capacity prevail; secondly, intramontanous planation surfaces and, thirdly, the peneplains of the forelands, both characterized by deeply-weathered saprolithic soils showing higher field capacities and nutrient contents. Therefore the plainland-units are more suitable for agriculture than the slopes. Notwithstanding the different land potentials, nowadays all parts of the Chaîne are affected by more or less intensive land use. Even the woodlands on the steep slopes are secondary forest, as detailed examinations of soil profiles reveal. These observations prove a long-term high population pressure on the land resources, which is in remarkable contrast to the low population density. Further human impact by population growth will increase soil degradation processes and aggravate the ecological conditions.